Entre penas e flechas: representações da temática indígena em livros diáticos de históriaa partir da lei nº 11.645/08 - Siqueira, Adriel Jonathas Fernandes (2019)
When we completed one decade of the law 11.645/2008 that obligates the teaching of the African, Afro-Brazilian and indigenous history and culture, we present a systematic study in a three didactic collection to Fundamental School and we looked for a balance about the indigenous representation inside History books. The collections “História Sociedaded & Cidadania”, “História nos Dias de Hoje” and “Integralis” were selected through the approval in the 2017 bid of the “Programa Nacional do Livro Didático“and we’ll be used in the schools of Mossoró/RN city. The schools are Escola Estadual José de Freitas Nobre, Escola Estadual Moreira Dias and Escola Estadual Monsenhor Raimundo Gurgel. As a main goal we have the analysis and comprehension of the representations historic/cultural of indigenous peole. And, among specific objectives, we mention a) the pathway of indigigenists and indigenous policies; b) The recognition of diversity of the brazilian indigenous culture; c) The study and comprehension of the contents which explain History and Culture of indigenous people in Brazil. The methodology used is based on Bardin (2016) thoughout content analysis. We analyzed the indigenous representations on texts and images shown in the history of Brazil. Therefore, we based on the concepts of Chartier (1988; 1990) and Hall (2015). Successively, on observation and problematization of images and we used Burke (2004). In relation to textbooks and their dimensions we strongly based on studies of Bittencourt (2002), furthermore, Munakata (2012). Regarding to cultural diversity we used the reference of Luciano (2016), data collected by The Brazilian Institute of Geography and Statistics through 2010 census and papers published by the historians Silva and Costa (2018). The representations analyzed on the research demonstrate the images of the indians that we have in our minds. There is still a wide use of images in the colonial period that produce stereotypes, among them the most recurrent is that of cannibalism. Images and texts that disappear in subsequent years and books of elementary school. Yet, despite some continuities, there are efforts by publishers that produce significant changes on the teaching of History and indigenous culture. The Law combined with teaching practices brought significant changes, but despite the path built there is much to do